A Comparative Overview of High Power Handling CMOS Switches and their Recent Applications in RF Front-Ends - Rascher, Jochen; Zohny, Amr; Glock, Stefan; Fischer, Georg; Weigel, Robert; Ußmüller, Thomas (14th Annual Wireless and Microwave Technology Conference (WAMICON), 2013)
In this publication techniques for high power handling capability (PHC) of RF switches in bulk CMOS are investigated and compared. Together with high isolation approaches these allow reconfigurable power amplifiers (PAs) or radio front-ends for Watt level communication standards. Special care is taken to assess the applicability of the solutions for monolithic integration in scaled CMOS processes. Results are shown with PHC as high as 34dBm in a 32nm CMOS process. Recent applications for the switches in front-ends or reconfigurable PAs are analyzed. They show large DC current reduction in back-off with stage bypassing and load adaptation concepts. Up to 50% DC current reduction for low output power is reported. This greatly improves the average PA efficiency for varying envelope signals without the efforts of more advanced solutions like envelope tracking.
elib2cris::1512001600,rascher2013